Relevansi Konsep Pendidikan Anak Menurut Abdullah Nashih Ulwan terhadap Pendidikan Karakter Islam Modern - Khairul Abdillah Harahap; Muh. Wasith Achadi; Bahtiar Arbi (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
The purpose of this study is to examine the relevance of Abdullah Nashih Ulwan’s concept of child education in Tarbiyat al-Aulad fi al-Islam to the development of modern Islamic character education. Ulwan emphasizes the importance of balanced development encompassing faith, morality, intellect, social awareness, and physical growth as the foundation for forming a holistic Islamic personality (syakhshiyyah islamiyyah). Employing a qualitative-descriptive approach through literature analysis, this study explores Ulwan’s five educational methods: exemplary behavior, advice and guidance, habituation, supervision, and educational punishment. The findings indicate that Ulwan’s educational principles remain relevant to contemporary character education models, such as those proposed by Thomas Lickona, which integrate cognitive, emotional, and behavioral dimensions. In the digital era, Ulwan’s educational values can be implemented through the ethical use of digital media, strengthening the moral roles of teachers and parents, and designing curricula that integrate spiritual and social dimensions. This study contributes to the academic discourse on Islamic moral education and provides a theoretical foundation for future research on the application of Ulwan’s ideas in technology-based learning environments